Global commodity markets and sovereign risk across 150 years - Domínguez-Cardoza, Angélica,Garamow, Adelina,Meyer, Josefin (DIW Berlin, German Institute for Economic Research, 2022)
How do commodity price movements affect sovereign default risk over the long-run? Using a novel dataset covering 41 countries and 42 raw commodities, we take a comprehensive long-run view to shed light on this so far understudied relationship between commodity risk and sovereign risk across 150 years. We create a novel country-specific commodity price index that allows us to take advantage of countries’ variation in their commodity export compositions. Our results are twofold: first, commodity price fluctuations show a persistent association with sovereign borrowing costs for countries that are commodity export dependent across the last one and a half centuries. Second, historically this relationship was driven by agricultural price movements; today it is driven by mineral and energy price movements.
urn:nbn:de:101:1-2023062704491975715563
Keywords: Graue Literatur; Sovereign Risk; Commodity prices